Peran Kepala Sekolah sebagai Pemimpin Transformasional di Sekolah Menengah Kejuruan - Widya Agustina, Dyan; Aprilia Wahyuli, Alma; Roma P Sianturi, Tama; Mariana Purba, Herina; Dwiyono , Yudo (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2024)
This study aims to analyze the role of the principal as a transformational leader in Vocational High Schools (SMK) and its impact on educational effectiveness. Qualitative research methods with a literature study approach are used to examine theories of transformational leadership and best practices in the context of education. Data were obtained through a literature review of relevant books, scientific journals, and official websites. Data analysis techniques using the Miles and Huberman method include data reduction, data presentation, and drawing conclusions. The study shows that principals who act as transformational leaders have the ability to inspire and motivate other members of the school community to achieve common goals, encourage innovation, and manage resources effectively. The study found that principals who play an effective transformational role not only set the direction and goals of teaching, but also significantly help improve the quality of teaching and prepare students for the world of work.. Keywords: Principal, Transformational Leader, SMK